Effect of transcutaneous electric nerve stimulation (TENS) on hormones profile in subjects with primary dysmenorrhoea - a preliminary study - S. R. A. Akinbo; B. A. Tella; A. J. Olisah; G. O. Ajayi; D. Alamu; B. Oshundiya (AOSIS, 2007)
Background & Objective: Primary dysmenorrhoea (PD) is defined as the occurrence of painful menstrual cramps of uterine origin which occurs in the absence of any underlying disease. The pathogenesis is unclear, but uterine hyperactivity, elevated prostaglandin and leukotrienes levels, and hormonal level fluctuations have all been implicated. The objective of this study was to evaluate the effect of TENS on the hormones cortisol and prolactin in individuals with PD. Methods: Plasma levels of cortisol and prolactin were studied in twenty-one (21) subjects with PD by obtaining blood samples from each subject pre-and post-TENS therapy on the first day of menstruation. The mean age of subjects was 23 (+ 2) years.  The Visual Analogue Scale (VAS) was used to assess the pre-and post-treatment pain intensity.  The TENS unit was applied for a duration of 30 minutes. Results: A paired t-test showed that there was an overall reduction in the mean cortisol and prolactin from  pre treatment values of 28.45µg/dl ((5.27) and 56.81ng/ml ((31.86) to post treatment values of 27.33µg/dl ((5.13) and 53.23ng/ml ((37.63) respectively. However, these differences were not statistically significant (P>0.05).  Pain intensity was significantly reduced comparing pre and post treatment VAS scores (P = 0.001). Conclusion: The probable mechanism by which TENS effected alterations in cortisol and prolactin levels and pain reduction in subjects with PD might be through the opioid-modulating analgesia system, which releases B-endorphins and other endogenous opiates in response to pain.  This is because there is a close relationship between B-endorphin, cortisol and neurons, which secrete dopamine into the hypothalamic-pituitary-portal system.